1990
DOI: 10.1111/j.1349-7006.1990.tb02667.x
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic Alteration of a Membrane‐associated Sialidase of Rat Liver

Abstract: Rat liver participate fraction contains two types of membrane‐associated and gangliosides‐hydrolyzing sialidase, which have been shown to be identical to two membrane‐associated sialidases of rat brain (I and II) chromatographically, immunologically and in substrate specificity. Chromatography on AH‐Sepharose 4B of the membrane sialidases of rat primary hepatoma induced by 3′‐methyl‐4‐dimethylaminoazobenzene (MeDAB) further revealed that hepatocarcinogenesis induces a marked decrease in sialidase II but no dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Using a differential assay procedure for each form, we observed that intra-lysosomal and membrane-bound sialidase activities were elevated, whereas cytosolic sialidase activity was reduced, in rat hepatomas as compared with normal liver. 52) In mouse epidermal JB6 cells exposed to TPA and in anchorage-independent transformants, we also found lysosomal sialidase activity to be decreased while plasma membrane-associated sialidase activity was increased as compared with that in untreated JB6 cells. 53) Reduction in lysosomal sialidase also occurred in rat 3Y1 fibroblasts after src-transformation, levels of activity inversely correlating with the metastatic potential.…”
Section: Aberrant Expression Of Sialidase In Cancersupporting
confidence: 48%
“…Using a differential assay procedure for each form, we observed that intra-lysosomal and membrane-bound sialidase activities were elevated, whereas cytosolic sialidase activity was reduced, in rat hepatomas as compared with normal liver. 52) In mouse epidermal JB6 cells exposed to TPA and in anchorage-independent transformants, we also found lysosomal sialidase activity to be decreased while plasma membrane-associated sialidase activity was increased as compared with that in untreated JB6 cells. 53) Reduction in lysosomal sialidase also occurred in rat 3Y1 fibroblasts after src-transformation, levels of activity inversely correlating with the metastatic potential.…”
Section: Aberrant Expression Of Sialidase In Cancersupporting
confidence: 48%
“…A more recent study demonstrated that high level of the plasma membrane sialidase ( NEU3 ) was linked to protection from apoptosis in colon cancer (Kakugawa et al., 2002). It has also been shown that activity of the lysosomal sialidase ( NEU1 ) appears to be enhanced in hepatomas in comparison to normal liver tissue, while the cytosolic sialidase ( NEU2 ) was generally less active in the malignant tissue (Miyagi et al., 1990, 1992). On the other hand, several studies have shown that sialidases might also possess anti‐metastatic properties (Kato et al., 2001; Miyagi et al., 1994; Sawada et al., 2002; Tokuyama et al., 1997), leaving the precise role for sialidases in tumor progression still to be explained.…”
Section: Glycosphingolipids and The Glycosynapsementioning
confidence: 99%
“…Several rat tissues, including the liver and brain were found to contain all the four types of sialidases. Based on the sialidase multiplicity, using a differential assay procedure for each form of sialidase, we observed that while the activity of the plasma membrane-bound sialidase was elevated, that of cytosolic sialidase was reduced in rat hepatomas as compared with the activity levels in the normal liver [10]. In mouse epidermal JB6 cells exposed to TPA and in their anchorage-independent transformants, we found lysosomal sialidase activity to be decreased and plasma membraneassociated sialidase activity to be increased as compared with the corresponding activities in the untreated JB6 cells [11].…”
Section: Introductionmentioning
confidence: 99%